PENGARUH DAYA PEMANASAN MICROWAVE OVEN TERHADAP KEKUATAN TARIK KOMPOSIT SERAT DAUN NANAS BERMATRIK EPOXY - Redi Bintarto; Moch. Syamsul Ma’arif; Fransisca Gayuh Utami Dewi; Sugiarto Sugiarto; Nurkholis Hamidi; Pudya Heryana (Scientific Journal of Mechanical Engineering Kinematika, 2021)
This study aims to determine the effect of microwave oven heating power on pineapple leaf fiber on the tensile strength of epoxy matrix composites. In this study, the composite reinforcement used was pineapple leaf fiber without treatment and pineapple leaf fiber heated using a microwave oven with 250W, 440W, and 715W power for 15 minutes after being given 6% NaOH immersion for 2 hours. The composite manufacturing method used is the vacuum assisted resin infusion method. Tensile testing was carried out on pineapple leaf fiber reinforced composite specimens according to ASTM D638-01 standard. The results showed that the higher the heating power of the microwave oven, the higher the tensile strength of the composite due to the better adhesion between the fiber and the epoxy matrix. The highest tensile strength was obtained in the pineapple leaf fiber-reinforced composite with a heating power of 715W of 147.9 MPa, then heating with a power of 440W of 136.6 MPa, heating with a power of 250W of 125.5 MPa, and the lowest on specimens of pineapple leaf fiber composite without treatment of 107.1 MPa. In addition, the SEM results also show that the surface roughness of the fiber increases with the addition of heating power and the wettability results also show that the wettability between the fiber and the epoxy matrix is ​​getting better as the heating power of the microwave oven increases.